Genetic Analysis of Glycoprotein Gene of Indonesian Rabies Virus - Susetya, Heru; Naoto, Ito; Sugiyama, Makoto; Minamoto, Nobuyuki (Universitas Gadjah Mada, 2005)
The amino acid sequences of the Glycoprotein gene (G gene) of field rabies virus SN01-23 from Indonesiawas determined. This isolate showed homology of 93% in the ectodomain of the Glycoprotein gene to that of theRC-HL strain, which is used for production of animal vaccine in Japan. The high identity in the ectodomainbetween this field isolate and strain RC-HL suggest that the rabies animal vaccine used in Japan will be effectivefor rabies street viruses in Indonesia. Result of phylogenetic analysis using the nucleotide sequences of the Ggenes of rabies street viruses showed that SN01-23 from Indonesia is more closely related to a rabies virus fromChina than to viruses from Thailand and Malaysia. This genetic data and historical background suggest thatrabies viruses in China had been transferred to Indonesia through dogs brought by humans migrating from Chinato Indonesia.Keywords : Rabies virus, Glycoprotein gene, Ectodomain, Phylogenetic analysis